Studying the cracking system in 17-18th century Portuguese Azulejos with SEM - Mimoso, J. (2010)
Portuguese glazed ceramic tiles - azulejos – are a distinctive mark of Portuguese culture. A review of azulejo pathologies throughout Portugal revealed that the most worrying forms of decay are related to defects that typically result from the manufacturing process and thus lie in wait in seemingly sound tiles until the proper conditions lead to the setting of decay. Our communication contains the SEM/EDS results of a study of cracking paths through the glaze and into the biscuit, and delamination patterns in the glaze-biscuit interface. The purpose is a better understanding of the fissural systems with a view to develop solutions that may prevent the onset of decay in fragile glazed tiles.